KARAKTERISTIK DAN BEBERAPA KANDUNGAN ZAT GIZI PADA LIMA SAMPEL MADU YANG BEREDAR DI SUPERMARKET - Mardhiati, Retno; Marliyati, Sri Anna; Martianto, Drajat; Madanijah, Siti; Wibawan, I Wayan Teguh (GIZI INDONESIA, 2020)
Honey is one of the herbal supplements for increasing body health. The nutrient content in honey products can be reduced due to its processing, packing, storage, and industrial process. This study aimed to analyze the characteristic of honey and some of its nutrient contents of 5 honey samples that disperse among the society. This study was conducted from March to September 2019 in the Ministry of Industry Centre for Agro-based Industry Laboratory, Bogor, East Java. Honey samples were obtained from some wholesale supermarkets around the Jakarta area. Total carbohydrate and energy testings were using IK 5.4.5 method. Water content, diastase enzyme activity, hydroxymethylfurfural (HMF) content, and acidity tests were using the Indonesian National StandardÂ  (SNI) procedure 3545 2013. HPLC method was used to test sucrose, glucose, and fructose, while AOAC 999.11 (9.1.09.2005 method was used to test Cu, Zn, and Fe content. Total carotenoid and flavonoid content were determined using spectrophotometry method.Â  The result revealed the characteristic of honey samples in this study, including the range of pH (3.56-4.16), water (17-22.9%), ashes (0,07-0,59), acidity (7.76-38.3 ml N NaOH 1/kg) and HMF (122-812 mg/kg) content as well as diastase enzyme activity (1.11-17.2 DN). Fructose, glucose, sucrose and reducing sugar content showed were, respectively, 21.5-39.3 gr/100 gr, 25.2-31.4 gr/100 gr, 0.5-1.75 gr/100 gr, and 58.4-71.2%. Honey samples contained 309-334 kal/100 gr of energy, 76.8-81.9% of carbohydrate, 0.03-0.39%, of protein and 0.10-0.65% of fat. Moreover, their mineral contents observed were 0.03-0.66 mg/kg of Cu, 0.09-3.13 mg/kg of Zn, and 1.59-20.1 mg/kg of Fe. Finally, total flavonoid and carotenoid of honey samples were, respectively, 0.02-0.07 %(b/b) and 0.05-0.64 mg/kg.